FEED POTENTIAL OF AGRICULTURE WASTE FOR BEEF CATTLE DEVELOPMENT IN KUNINGAN REGENCY, WEST JAVA - Farda, F. T.; Laconi, E. B.; Mulatsih, S. (Diponegoro University, 2015)
The aims of research were to identify and analyze potential agricultural waste used as feed, examines the characteristics of beef cattle ranchers and estimate the ability of the addition of beef cattle population in Kuningan Regency. The primary data were taken from interviews with 30 respondents beef cattle farmers selected by purposive sampling in three districts based on the largest beef cattle population as a recommendation by local government of Kuningan Regency Agricultural. Waste samples taken randomly three times to analyze of nutrient composition by proksimat analyze was the type of the most widely used for feed. Secondary data was obtained from Kuningan Regency Veterinary Office, Department of Food Crops and the Central Statistics Agency. The results showed that the type of agricultural waste used in Kuningan Regency from highest to lowest production is rice straw, hay sweet potatoes, peanuts and hay with traditional animal husbandry systems. Districts that can improve beef cattle population from the highest to lowest number was Luragung, Cibingbin, Ciwaru, Subang, Maleber, Cibeureum, Cilebak, Karangkancana and Cimahi. In conclusion, the highest agricultural waste production was rice straw and the highest potential for the development of beef cattle in the Kuningan Regency was Luragung District.